A Discrete Cobalt Complex Obtained from a 1 D Coordination Polymer for Highly Selective Sensing of the Mercury(II) Ion. Issue 7 (26th May 2014) - Mishra, Anurag; Jo, Jae‐Ho; Kim, Hyunuk; Woo, Sangkook; Chi, Ki‐Whan
Abstract A unique structural transformation in a 1 D chain coordination network 2 is converted to a discrete compound 3 accompanied by a change in the ion‐exchange system. Remarkably, 3 produced a turn‐on fluorescence and selective sensing for Hg2+, whereas other ions, such as K+, Mg2+, Ca2+, Mn2+, Fe2+, Co2+, Ni2+, Cu2+, Zn2+, and Cd2+, did not show any notable effects. Thus, the Hg2+‐selective fluorescent chemosensor was free from interference by competing metal ions.